MANAJEMEN KURIKULUM PROGRAM ONE DAY BOARDING SCHOOL DI MTS MUHAMMADIYAH 1 TAMAN SIDOARJO - MAULANI RAHMAWATI.S, ARBIAH; SYAHIDUL HAQ, MOHAMMAD (Inspirasi Manajemen Pendidikan, 2019)
This one day boarding school program has the aim to shape the character of students, to provide deepening of Islamic values ??and self-development for students. The purpose of this study was to find out the design, implementation, monitoring and evaluation of the curriculum for the one day boarding school program at MTs Muhammadiyah 1 in Taman Sidoarjo. This research is a qualitative study using case study design. The subject of this study consisted of principals, vice principals, teachers, and students. Data collection using interview, observation, and documentation techniques. Data analysis is done by collecting data, conducting condensation, presenting data, conducting verification, then drawing conclusions. The validity test of the data is done through a test of credibility, reliability, dependability and confirmation. The results of this study are as follows. (1) curriculum design of the one day boarding school program in the implementation of activities in the form of diniyah, congregational prayers, tadarus al-quran, tahfidz al-quran & murojaah, public speaking / muhadhoroh, motivation / self-development, knitting, Arabic conversation and English, tadabbur nature (traveling), and sports; (2) the implementation of the one day boarding school program curriculum is attended by all students from the seventh to ninth grade (required), the teacher is also involved with the assignment to fill the material in one day boarding school activities which are conducted every two weeks on Friday until with Saturday morning; (3) monitoring and evaluation of curriculum for the one day boarding school program at MTs Muhammadiyah 1 Taman Sidoarjo is held by teachers every once a week as a form of evaluation. When evaluations are carried out in need of parents, the meeting is conducted with a student guardian association or IWAMA (the guardian bond of the madrasa students). Keywords: one day boarding school, diniyah, murojaah Program one day boarding school ini memiliki tujuan untuk membentuk karakter peserta didik, memberikan pendalaman nilai-nilai Islam maupun pengembangan diri untuk peserta didik. Tujuan dari penelitian ini untuk mengetahui desain, implementasi, monitoring dan evaluasi kurikulum program one day boarding school di MTs Muhammadiyah 1 Taman Sidoarjo. Penelitian ini merupakan penelitian kualitatif dengan menggunakan desain studi kasus. Subjek penelitian ini terdiri dari kepala sekolah, wakil kepala sekolah, guru, dan peserta didik. Pengumpulan data dengan menggunakan teknik wawancara, observasi, dan dokumentasi. Analisis data dilakukan dengan mengumpulkan data, melakukan kondensasi, menyajikan data, melakukan verifikasi, kemudian menarik kesimpulan. Uji keabsahan data dilakukan melalui uji kredibilitas, transferabilitas, dependabilitas dan konfirmabilitas. Hasil dari penelitian ini adalah sebagai berikut. (1) desain kurikulum program one day boarding school dalam pelaksanaan kegiatannya berupa diniyah, sholat berjamaah, tadarus al-qur?an, tahfidz al-qur?an & murojaah, public speaking/ muhadloroh, motivasi/ pengembangan diri, tahajud, percakapan bahasa arab dan bahasa inggris, tadabur alam (jalan-jalan), dan olahraga; (2) implementasi kurikulum program one day boarding school diikuti oleh seluruh peserta didik dari kelas tujuh sampai dengan kelas sembilan (diwajibkan), guru juga terlibat dengan diberi tugas untuk mengisi materi dalam kegiatan one day boarding school yang dilakukan dua minggu sekali pada hari jumat sampai dengan sabtu pagi; (3) monitoring dan evaluasi kurikulum program one day boarding school di MTs Muhammadiyah 1 Taman Sidoarjo dilakukan rapat oleh guru setiap seminggu sekali sebagai bentuk evaluasi. Ketika evaluasi yang dilakukan membutuh orang tua, maka rapat dilakukan dengan perkumpulan wali murid atau IWAMA (ikatan wali murid madrasah). Kata Kunci: one day boarding school, diniyah, murojaah